Ganti Kerugian Pengadaan Tanah Untuk Pembangunan Jalan Tol Di Wilayah Perkotaan (Studi Kasus Pengadaan Tanah Jalan Tol Bogor Ring Road Seksi IIIB di Kelurahan Kayumanis Kecamatan Tanah Sareal Kota Bogor) - Triana; Kasman (Magister Kajian Pembangunan Perkotaan dan Wilayah, 2024)
One of the challenges in developing toll road infrastructure in urban areas is population density and limited space. Space limitations are an important issue in providing land for toll road construction in urban areas. The limited availability of land makes it difficult for residents affected by development to buy land or houses again if the compensation value they receive does not match the market value or is even far below the market value. The Bogor Ring Road Toll Road is a development project for the public interest located in the Bogor City area. The understanding circulating in the community is that the compensation received is profit compensation whose value is many times the market value of the NJOP. Normatively there is no profit compensation in land acquisition but it is known as Fair Replacement Value (NPW). The aim of this research is to analyze the components that make up NPW, the difference in the physical value of land between NPW, ZNT Map and NJOP, as well as the market value of land plots per plot of land in NPW, ZNT map and NJOP. The research methodology is a mixed method which combines two research methods, namely qualitative and quantitative. The land market value of the ZNT map is obtained using a spatial method, namely by overlaying two maps, namely the toll road alignment map and the ZNT map (Bhumi ATR). The NJOP land market value is taken from the PBB SPPT land parcel. NPW market value is based on adjustments made by the appraiser. Affected communities need to know the differences in market value and the components that make up NPW as compensation for losses given so that it can be well received.